Diet, nutrition and the prevention of cancer - Key, Timothy J; Schatzkin, Arthur; Willett, Walter C; Allen, Naomi E; Spencer, Elizabeth A; Travis, Ruth C (Public health nutrition, 2004)
To assess the epidemiological evidence on diet and cancer and make public health recommendations. Review of published studies, concentrating on recent systematic reviews, meta-analyses and large prospective studies. Overweight/obesity increases the risk for cancers of the oesophagus (adenocarcinoma), colorectum, breast (postmenopausal), endometrium and kidney; body weight should be maintained in the body mass index range of 18.5-25 kg/m(2), and weight gain in adulthood avoided. Alcohol causes cancers of the oral cavity, pharynx, oesophagus and liver, and a small increase in the risk for breast cancer; if consumed, alcohol intake should not exceed 2 units/d. Aflatoxin in foods causes liver cancer, although its importance in the absence of hepatitis virus infections is not clear; exposure to aflatoxin in foods should be minimised. Chinese-style salted fish increases the risk for nasopharyngeal cancer, particularly if eaten during childhood, and should be eaten only in moderation. Fruits and vegetables probably reduce the risk for cancers of the oral cavity, oesophagus, stomach and colorectum, and diets should include at least 400 g/d of total fruits and vegetables. Preserved meat and red meat probably increase the risk for colorectal cancer; if eaten, consumption of these foods should be moderate. Salt preserved foods and high salt intake probably increase the risk for stomach cancer; overall consumption of salt preserved foods and salt should be moderate. Very hot drinks and foods probably increase the risk for cancers of the oral cavity, pharynx and oesophagus; drinks and foods should not be consumed when they are scalding hot. Physical activity, the main determinant of energy expenditure, reduces the risk for colorectal cancer and probably reduces the risk for breast cancer; regular physical activity should be taken.